2010
DOI: 10.1002/eji.200939865
|View full text |Cite
|
Sign up to set email alerts
|

GITR contributes to the systemic adjuvanticity of the Escherichia coli heat‐labile enterotoxin

Abstract: The Escherichia coli heat-labile enterotoxin (LT) possesses a powerful mucosal and systemic adjuvant effect. However, little is known about the cellular and molecular basis of the immunostimulatory activity of LT at the mucosal level, and even less information is available on the mechanisms underlying its systemic adjuvant activity. In this study, we show that distinct mechanisms are responsible for the parenteral and mucosal adjuvanticity of LT. Indeed, the systemic administration of LT upregulates the expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Moreover, the CTB subunit may be responsible for the CT’s ability to induce Th17-dominated responses which is in contradiction with the tolerogenic role of CTB. Another study by Tamayo et al [36] demonstrated that LT upregulates the expression of the glucocorticoid-induced TNFR-related protein (GITR) in CD4 + T cells, that may contribute to adjuvanticity by acting as an activation-induced costimulatory signal in CD4 + CD25 - cells. Of note, this effect was observed after systemic but not mucosal administration of LT, thus demonstrating that the mechanisms of adjuvanticity of LT are influenced by the route of administration.…”
Section: Adjuvanticity Of Cholera-like Enterotoxinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the CTB subunit may be responsible for the CT’s ability to induce Th17-dominated responses which is in contradiction with the tolerogenic role of CTB. Another study by Tamayo et al [36] demonstrated that LT upregulates the expression of the glucocorticoid-induced TNFR-related protein (GITR) in CD4 + T cells, that may contribute to adjuvanticity by acting as an activation-induced costimulatory signal in CD4 + CD25 - cells. Of note, this effect was observed after systemic but not mucosal administration of LT, thus demonstrating that the mechanisms of adjuvanticity of LT are influenced by the route of administration.…”
Section: Adjuvanticity Of Cholera-like Enterotoxinsmentioning
confidence: 99%
“…However, whether these effects render effector T cells unresponsive to suppression and/or lead to Treg inhibition has not been demonstrated. Similarly, GITR, which is upregulated by systemic administration of LT [36], may also help target cells to evade suppression or inhibit the suppressive capacity of Tregs, but as for costimulatory molecules, a direct impact of LT on Tregs has not been demonstrated. Anjuere et al [62] found that oral administration of CT to mice resulted in a marked increase in PP and MLN of CD11c + CD8 int DC with potent immunological antigen presentation, together with inhibition of the normal development of tolerogenic CD11c + CD8 + B220 + (plasmacytoid) DC in response to CTB administration, but again, inhibition of Tregs was not reported.…”
Section: Cholera-like Enterotoxins and Tregsmentioning
confidence: 99%